Prevalence of Anterior Femoral Neck Osteophyte in a Total Hip Arthroplasty Population: Analysis of Preoperative Surgical Plans - Adam M. Katchky; Mitchell L. Smith; Andrew J. Shimmin; Stephen J. McMahon; Jeremy Latham; Jonathan V. Baré (Advances in Orthopedics)
Despite strongly positive results of total hip arthroplasty (THA), patients remain at risk for complications including dislocation. Spinopelvic motion and the hip-spine relationship have been recognized as important factors in surgical planning and implant positioning in THA. Periarticular osteophytes are one of the hallmark pathoanatomic features of osteoarthritis and may influence implant positioning and joint stability; residual osteophytes at the anterior femoral neck may cause anterior impingement and posterior instability. No studies have been identified which establish the prevalence of anterior femoral neck osteophyte for incorporation into THA planning. 413 consecutive patients scheduled for THA underwent preoperative planning taking into account spinopelvic motion to establish optimal component position. Each surgical plan was reviewed retrospectively by four independent raters who were blinded to other imaging and intraoperative findings. Anterior femoral neck osteophytes were rated as being absent, minor, or extensive for each case. A single outlying rater was excluded. Inter-rater reliability was calculated manually. The patient group comprised 197 male and 216 female hips, with a mean age of 63 years (range 32–91). The presence of anterior femoral neck osteophytes was identified in a mean of 82% of cases (range 78–86%). A significant number of patients were found to have large or extensive osteophytes present in this location (mean 27%; range 23–31%). Inter-rater reliability was 70%. A large majority of our THA patients were found to have anterior femoral neck osteophytes. These must be considered during preoperative planning with respect to the spinopelvic relationship. Failure to identify and address osteophytes intraoperatively may increase the risk of impingement in flexion and/or internal rotation, leading to decreased range of motion, joint instability, and possibly dislocation. Planned future directions include incorporation of an impingement and instability model into preoperative planning for THA.